Nutritional Composition of Seaweed Kappaphycus alvarezii - Khotijah, Siti; Irfan, Muhammad; Muchdar, Fatma (Agrikan Jurnal Agribisnis Perikanan, 2020)
Seaweed is one of the important marine commodities and is a leading commodity. Seaweed K. alvarezii is a type of carrageenan-producing seaweed, as a food source for humans, pharmaceutical ingredients, as a thickener, stabilizer and emulsion.Carrageenan is used in food products, pharmaceuticals, textile cosmetics, toothpaste and other industries. Seaweed has a fairly complete nutritional content. Chemically seaweed consists of water (27.8%), protein (5.4%), carbohydrate (33.3%), fat (8.6%), crude fiber (3%), and ash (22.5%). This review article aims to reveal the nutritional composition of seaweed K. alvarezii, especially protein, amino acids, fat, ash content, minerals and vitamins. Seaweed K. alvarezii has nutritional composition values such as protein, amino acids, fat, ash content, minerals and vitamins that vary in nutritional value.